Combined glucose ingestion and mouth rinsing improves sprint cycling performance - Chong, E.; Guelfi, K. J.; Fournier, P. A. (International Journal of Sport Nutrition and Exercise Metabolism, 2014)
This study investigated whether combined ingestion and mouth rinsing with a carbohydrate solution could improve maximal sprint cycling performance. Twelve competitive male cyclists ingested 100 ml of one of the following solutions 20 min before exercise in a randomized double-blinded counterbalanced order (a) 10% glucose solution, (b) 0.05% aspartame solution, (c) 9.0% maltodextrin solution, or (d) water as a control. Fifteen min after ingestion, repeated mouth rinsing was carried out with 11 × 15 ml bolus doses of the same solution at 30-s intervals. Each participant then performed a 45-s maximal sprint effort on a cycle ergometer. Peak power output was significantly higher in response to the glucose trial (1188 ± 166 W) compared with the water (1036 ± 177 W), aspartame (1088 ± 128 W) and maltodextrin (1024 ± 202W) trials by 14.7 ± 10.6, 9.2 ± 4.6 and 16.0 ± 6.0% respectively (p < .05). Mean power output during the sprint was significantly higher in the glucose trial compared with maltodextrin (p < .05) and also tended to be higher than the water trial (p = .075). Glucose and maltodextrin resulted in a similar increase in blood glucose, and the responses of blood lactate and pH to sprinting did not differ significantly between treatments (p > .05). These findings suggest that combining the ingestion of glucose with glucose mouth rinsing improves maximal sprint performance. This ergogenic effect is unlikely to be related to changes in blood glucose, sweetness, or energy sensing mechanisms in the gastrointestinal tract